1991
DOI: 10.1139/x91-133
|View full text |Cite
|
Sign up to set email alerts
|

Repeated measures experiments in forestry: focus on analysis of response curves

Abstract: Treatment effects over time are frequently investigated using repeated measures designs, but analyses of these experiments frequently fail to address a primary objective of collecting data over time, namely description of the response curve. The analysis advocated in this paper utilizes the intrinsic continuity of the repeated measures factor by focusing on response curves. Treatments are compared by analyzing estimated coefficients of response curves proposed by the investigator. This approach provides more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 0 publications
0
79
1
5
Order By: Relevance
“…As the test for trend in accuracy over time is based on b, the test is limited to assessing the linear component of the relationship of accuracy with time (year). The test for trend is a repeated measures analysis [28] implemented as a parametric test using a one-sample t-test applied to the sample b m,ss observations (the sample size is n ss =number of study sites). Alternatively, a non-parametric version of the test for trend could be implemented using the one-sample non-parametric Wilcoxon test applied to the sample b m,ss observations.…”
Section: Temporal Stability Assessmentmentioning
confidence: 99%
“…As the test for trend in accuracy over time is based on b, the test is limited to assessing the linear component of the relationship of accuracy with time (year). The test for trend is a repeated measures analysis [28] implemented as a parametric test using a one-sample t-test applied to the sample b m,ss observations (the sample size is n ss =number of study sites). Alternatively, a non-parametric version of the test for trend could be implemented using the one-sample non-parametric Wilcoxon test applied to the sample b m,ss observations.…”
Section: Temporal Stability Assessmentmentioning
confidence: 99%
“…genotype pair ; the sub-unit in the splitplot design) and were analysed using orthogonal Whole experimental units were the open-top chambers (n l 32) and the subunits were half-chambers consisting of early or late leaf-fall genotype pairs (Gen pair). Corresponding data are shown in Figures 1 and 4. polynomials in repeated measure  to characterize treatmentitime interactions over the duration of the experiment (Meredith & Stehman, 1991). Coefficients of second-order polynomials were calculated according to Robson (1959) for data with unequal sample spacing.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For example, a significant linear CO # effect (i.e., a significant CO # itime interaction) for fine root production indicated that the rate of fine root production was significantly affected by atmospheric CO # concentration (cf. Meredith & Stehman, 1991). To analyse treatment effects on fine-root life span, cohort survivorship functions were tested using a Gehen-Wilcoxon test for survivorship data in which not all subjects die before the end of the experiment (Pyke & Thompson, 1986).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Such a problem can be overcome by fitting the same regression model separately to the data from each experimental unit and then comparing the resulting parameter estimates indirectly by using them as primary data for multivariate analysis (e.g., Fleming and Wood 1996). This allows one to use the preferred regression-based approach without foundering on the autocorrelation in the observations (Meredith and Stehman 1991). Autoregression analysis (e.g., Chatfield 1989) represents another approach to the autocorrelation problem.…”
Section: Autocorrelationmentioning
confidence: 99%